2013
DOI: 10.1109/tvcg.2012.131
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Dependent Vector Field Topology Based on Streak Surfaces

Abstract: It was shown recently how the 2D vector field topology concept, directly applicable to stationary vector fields only, can be generalized to time-dependent vector fields by replacing the role of stream lines by streak lines. The present paper extends this concept to 3D vector fields. In traditional 3D vector field topology separatrices can be obtained by integrating stream lines from 0D seeds corresponding to critical points. We show that in our new concept, in contrast, 1D seeding constructs are required for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…This colormap aids the identification of velocity magnitude values on 3D surfaces. Üffinger et al [101] apply a white to green sequential colormap to show hyperbolicity of path surfaces and a white to blue sequential colormap for the finite-time Lyapunov exponent (FTLE) representation. These colormaps are used for the comparison of the vector field attributes.…”
Section: Colormap Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This colormap aids the identification of velocity magnitude values on 3D surfaces. Üffinger et al [101] apply a white to green sequential colormap to show hyperbolicity of path surfaces and a white to blue sequential colormap for the finite-time Lyapunov exponent (FTLE) representation. These colormaps are used for the comparison of the vector field attributes.…”
Section: Colormap Applicationsmentioning
confidence: 99%
“…By analyzing tasks associated with the colormaps, many applications utilize colormaps to carry out multiple tasks. They use multiple colormaps to cope with these tasks, 16 papers ([1], [2], [7], [14], [38], [39], [53], [54], [59], [63], [68], [69], [87], [98], [99], [101]) utilize more than one type of colormap for different data or tasks in their visualizations. Furthermore, many works, for example, [6], [8], [14], [37], [59], [69], require combined tasks to be performed with a single colormap.…”
Section: Colormap Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A repelling LCS is a material structure that repels all particles, whereas an attracting LCS attracts them [Hal01]. A number of variants to LCS calculation have been proposed in the literature, including localized FTLE [KPH * 09], a method based on streak surfaces [ÜSE13] and time line cell tracking [KER * 14]. Haller [Hal01] has demonstrated that LCS can be extracted as ridges of the finite-time Lyapunov exponent (FTLE) field.…”
Section: Inertial Particles In Visualizationmentioning
confidence: 99%
“…This concept has been extended to 3D unsteady attracting and repelling manifolds by Üffinger et al . [USE12].…”
Section: Related Workmentioning
confidence: 99%